2020
DOI: 10.1167/iovs.61.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Monocular Luminance Increases Monocular Temporal Synchrony Threshold in Human Adults

Abstract: The purpose of this study was to present our investigation of the influence of reduced monocular luminance on monocular and dichoptic temporal synchrony processing in healthy adults. METHODS. Ten adults with normal or corrected to normal visual acuity participated in our psychophysical study. The temporal synchrony threshold in dichoptic (experiment 1), monocular (experiment 2), and binocular (experiment 3) viewing configurations was obtained from each observer. Four flickering Gaussian dots (one synchronous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Similar to previous studies, 20,24 for the three psychometric functions from each observer, an F-test indicated that the full model (with different slopes across different configurations) and the reduced model (with the same slopes across different configurations) were not statistically different. Hence, we assumed that the psychometric slopes were equal across the three configurations for each observer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to previous studies, 20,24 for the three psychometric functions from each observer, an F-test indicated that the full model (with different slopes across different configurations) and the reduced model (with the same slopes across different configurations) were not statistically different. Hence, we assumed that the psychometric slopes were equal across the three configurations for each observer.…”
Section: Discussionsupporting
confidence: 80%
“…A similar paradigm to previous studies 20,24,25 was used to measure the temporal synchrony threshold in this study. Two pairs of Gaussian dots were shown in the task: the reference pair flickered synchronously, while the signal pair flickered asynchronously.…”
Section: Designmentioning
confidence: 99%
“…A brief light reduction induces a significant delay in the previously dimmed eye Seung Hyun Min 1,2 | Alexandre Reynaud 1 | Robert F. Hess 1 be demonstrated in visually impaired individuals due to anatomical or neural pathologies that produce interocular imbalances. For example, unilateral cataract reduces the light transmission through the affected crystalline lens.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…However, the luminance level between the eyes has to be equal for optimal visual processing. Otherwise, binocular balance, 1 interocular temporal synchrony 2 and depth perception 3 are compromised. For example, the difference in the interocular light level can induce the Pulfrich effect, which is a century‐old illusion of depth in the absence of disparity 4 .…”
Section: Introductionmentioning
confidence: 99%